Theological reflections on compadrazgo [1973] - Sánchez-Arjona, Rodrigo (2007)
At the annual meetings of the I.P.A. we have frequently spoken about the compadrazgo spread among our peasants everywhere; some praise it, most would like to see it extinguished once and for all, because they see in it one more way of social exploitation.